Health promotion and health education in schools (One Health & Risk Management, 2021)
Introduction. Health education at the school level is one of the main objectives of promoting a correct education on various aspects of health; at the same time forming indispensable attitudes and skills for a responsible and a healthy behavior for children. In the Republic of Moldova, health education is an optional course taught in schools, from the first to the twelfth grade, using age-appropriate programs and teaching materials for each educational cycle. There are several arguments in favor of health education in schools, one of them being the educational activity itself as a means for informing children and adolescents about different areas of culture and science, in parallel with the development of practical skills. In this sense, health education, as part of the medical sciences, aims not only to transmit a scientifically correct information to students, but also to create specific healthy individual behaviors, attitudes corresponding to the educational ideal.Material and methods. The study was conducted in the period of September -December 2019 within 4 educational institutions. The study instrument included one questionnaire with 34 questions regarding health promotion and health education in schools. The curricula of the school discipline “Personal Development” and 20 teachers who were involved in teaching this class served as object of study. The data were analyzed trough Microsoft Excel and Epi Info 7.Results. The assessment of the aims and objectives of this discipline determined that teachers pay less attention to the consultation regarding personal, family and community health, namely 60% in the primary classes and 40% in the gymnasium and high school classes, respectively, thus confirming the fact that teachers are not specialists in the field and are not involved in teaching this subject. Evaluation of the secondary data obtained following the questioning of the teachers from pre-university institutions, revealed that they strictly follow the curriculum for the course "Personal Development"; they hold the specific competences to teach this course and provide instruction and information to pupils in regard to different health issues, such as alcohol, drugs, tobacco, proper nutrition, physical activity, pregnancy prevention, prevention of sexually transmitted infections, HIV/AIDS, sex education, emotional health, stress avoidance, suicide prevention, prevention of violence and aggression, personal safety , prevention of food poisoning, depending on the pupils’ age. Teachers strongly believe that this course is very important and necessary to be taught in schools. They strictly comply with the class schedule. Unfortunately, most teachers (80%) mentioned that they do not collaborate with local health departments and health organizations. Also, the relationship between family and school is not seen as a close one, especially in gymnasium and high school classes. The major problem is that instructors, who are involved in teaching subjects related to health education are not certified in this field.Conclusions. Health education among students is necessary for raising awareness on health issues in terms of understanding the importance of hygienic behavior, promotion of healthy lifestyle and adopting a risk-free behavior. Moreover, it is crucial to develop an active position towards individual health and public health issues.